STRATEGI KREATIF DALAM PEMBUATAN IKLAN LAYANAN MASYARAKAT ‘’BENGKULU POROS MARITIM DUNIA’’ DI BENGKULU EKSPRESS TELEVISI - Ekky Muhardani; Linda Astuti; Vethy Octaviani (UNIVED PRESS, Universitas Dehasen Bengkulu, 2018)
The type of research that will be used in this research is qualitative descriptive research. This research is limited to the disclosure of a problem or event as it is in just to reveal the facts so that the result is emphasized in the description objectively or as is about the object under study. In this study a qualitative descriptive type was used to describe how the creative strategy of Community Service Ads